Increasing the targeting scope and efficiency of base editing with Proxy‐BE strategy. Issue 8 (29th December 2019) - Liu, Yin; Li, Guanglei; Yang, Guang; Gu, Huifeng; Huang, Shisheng; Yu, Wenxia; Qin, Guizhen; Liu, Xinyi; Zhou, Fuling; Huang, Xingxu; Wei, Yongchang
Abstract : Base editors (BEs) are widely used in precise gene editing due to their simplicity and versatility. However, their efficiencies are hindered by various obstacles. Considering the chromatin microenvironment as a possible obstacle, here, we demonstrate a further development of the proxy‐clustered regularly interspaced short palindromic repeats strategy, termed Proxy‐BE, to increase gene editing efficiency. Specifically, a nuclease‐dead Cas9 (dCas9) was bound to the sequence about 20–30 base pair away from the target site, potentially improving access to the DNA and, thus, providing a better editing microenvironment for base editors. Our findings confirm that nuclease‐dead Streptococcus pyogenes Cas9 can assist the base editors SaKKH‐BE3 and dCpf1‐BE to double their canonical base editing efficiency. This work provides a new approach to enhance base editing, extending its scope for biological research and gene therapy. Abstract :